2010
DOI: 10.3354/meps08517
|View full text |Cite
|
Sign up to set email alerts
|

Fucus vesiculosus and spiralis species complex: a nested model of local adaptation at the shore level

Abstract: Intertidal rocky shores provide classic examples of habitat-driven divergent selection. We show that the species complex Fucus vesiculosus L./F. spiralis L. is composed of 3 distinct genetic entities that have evolved along different time scales. Using assignment tests based on microsatellite markers and performed on randomly sampled individuals in 2 separate geographic regions (Portugal and France), we reveal that F. spiralis consists of 2 genetic entities that have distinct vertical distributional patterns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(111 citation statements)
references
References 56 publications
6
105
0
Order By: Relevance
“…Sampling method and original source (see Section 2.2) for F. spiralis: 1, this study; 2, this study; 3, Perrin et al (unpub. );4, Billard (2007) and Billard et al (2010 in the South) the transect was taken in the middle of the F. spiralis zone (this study). Method 3 utilized samples from two locations per site, separated by 100-200 m (see Engel et al, 2005) whose taxon identity had been previously confirmed by microsatellite genotyping (Perrin et al, unpub.…”
Section: F Spiralismentioning
confidence: 99%
See 4 more Smart Citations
“…Sampling method and original source (see Section 2.2) for F. spiralis: 1, this study; 2, this study; 3, Perrin et al (unpub. );4, Billard (2007) and Billard et al (2010 in the South) the transect was taken in the middle of the F. spiralis zone (this study). Method 3 utilized samples from two locations per site, separated by 100-200 m (see Engel et al, 2005) whose taxon identity had been previously confirmed by microsatellite genotyping (Perrin et al, unpub.…”
Section: F Spiralismentioning
confidence: 99%
“…data, Engel et al, 2005 for Gris Nez). In Method 4, we selected individuals previously determined by microsatellite genotyping (in order to avoid hybrids) as F. spiralis High, F. spiralis Low (or as F. vesiculosus) that had been collected along a vertical transect on the shore or with random coordinates (a subset of individuals from Billard et al (2010) and also from Billard (2007) for Viana).…”
Section: F Spiralismentioning
confidence: 99%
See 3 more Smart Citations